"Nothing Will Ever Be the Same" – Seven Years After the Terror Attacks on New York, A New Interdisciplinary Collection of Essays Takes Stock of the Creative Processing of 9/11 (KULT_online, 2009)
Edited by Ingo Irsigler and Christoph Jürgensen, Nine Eleven: Ästhetische Verarbeitungen des 11. September 2001 examines artistic handlings of the events of 9/11 over the course of 17 essays. From an intercultural and interdisciplinary standpoint, the volume investigates literary, audiovisual, and pop culture treatments of the media event "September 11th." Individual chapters scrutinise the specific forms and functions of performances, based on the understanding that literary, visual, and dramatic treatments constitute a cultural processing dynamic. On the whole, these studies of media-specific mechanisms and typologies are demanding and highly relevant; they offer a current appraisal that balances artistic readings and meaning creation in view of an event that has been deemed a cultural caesura.